Upaya Qismu Ri’ayah dalam Pelaksanaan Bimbingan dan Konseling Bagi Santri Pondok Pesantren - Syafiq, Mohamad; Mohammad, Salavi (Al-Jadwa: Jurnal Studi Islam, 2023)
Guidance and counseling is an activity of providing assistance to other people to help them solve a problem they have. Darullughah Wadda'wah Islamic Boarding School is an Islamic educational institution that has thousands of students, To carry out supervision on each individual student is not an easy thing, then a section (qism) was formed called the supervisory section (qismu ri'ayah) which aims to carry out supervision through a "ro'i" (management) who is responsible for several "roiyyah" (students) in helping to solve problems and directing them. to become a better individual. The purpose of this research is to determine the implementation of Islamic guidance and counseling at the Darullughah Wadda'wah Islamic boarding school which is carried out by Qismu Ri'ayah. This research uses a qualitative approach with the type of research, namely case study. The results of the research concluded that the implementation of guidance and counseling for students at the Darullughah Wadda'wah Islamic boarding school was carried out through ri'ayah activities by Ro'I (management) to Roiyyah (students) with responsive services on the personal, social, learning and career aspects of the students